(977) دور التكاليف والمبيعات والأرباح والأسعار فى إدارة تخطيط الوحدات والمجمعات الإنتاجية The role of costs, sales, profits, and prices in managing the planning of production units and complexes. - ترجمة: محمد عدلي عبد المنعم ، مراجعة: محمد عبد الفتاح منجي (معهد التخطيط القومي, 2026)
ملخص تنتمي هذه المذكرة إلى أدبيات الاقتصاد المخطط وتتناول آليات رفع كفاءة الوحدات الإنتاجية في النظم الاشتراكية، مع إسقاط مستهدفاتها على القطاع العام المصري. يتلخص المحتوى في المحاور المحاسبية والإنتاجية التالية: الربح الصافي كمؤشر مركب للكفاءة: تعتبر المذكرة "الربح الصافي" المؤشر الحاسم والعمود الفقري للنظام المحاسبي؛ لكونه يعكس الفرق بين الإيرادات والتكاليف الذاتية بعد سداد الفوائد المستحقة للدولة مقابل رأس المال. ويقيس هذا المؤشر قدرة الإدارة على خفض التكاليف، تقصير دورة رأس المال، ورفع الإنتاجية. أبعاد الاقتصاد الخارجي والتصدير: تؤكد الدراسة ضرورة دمج نتائج التجارة الخارجية والأسواق العالمية في النظام المحاسبي للوحدات الإنتاجية. وترى أن خفض التكاليف ورفع جودة السلع هما السبيل لتعزيز تنافسية المنتجات دولياً، مع الإشارة إلى دور الدعم الحكومي المؤقت والتنازلي لمعالجة خسائر التصدير وتحفيز الإنتاج المتوافق مع المعايير العلمية العالمية. ديناميكية الأسعار الصناعية والتخطيط: يُطرح السعر كأداة تعبير نقدي عن قيمة العمل الاجتماعي ومقياس لترشيد الإنفاق. وتدعو المذكرة إلى التنسيق بين التخطيط المركزي للدولة (الذي يحدد الخطوط العريضة لسياسة الأسعار) وبين الإدارة الذاتية والمادية للمجمعات الإنتاجية لضمان المرونة والاستجابة لآليات السوق والتغذية الراجعة من المستهلكين. This academic memorandum originates from socialist planned economy literature, exploring mechanisms to enhance production unit efficiency, with implications for the Egyptian public sector. The study conceptualizes core accounting and operational pillars as follows: Net Profit as a Composite Efficiency Metric: The document identifies "Net Profit" as the backbone of the accounting system and a decisive indicator for tracking performance. It serves as a composite measure reflecting the gap between revenues and self-costs (operating expenses) after deducting state-imposed capital interests. Maximizing net profit directly correlates with cost reduction, accelerated capital turnover, and heightened productivity. External Economy and Export Dynamics: A key contribution is the integration of external trade and global market conditions into local accounting frameworks. The analysis emphasizes that lowering production self-costs and upgrading technical quality are prerequisites for global competitiveness. Furthermore, it addresses temporary, regressive state subsidies designed to absorb export losses and stimulate globally competitive production. Industrial Pricing and Decentralized Planning: Price is defined as the monetary expression of socially necessary labor and a tool for optimizing expenditures. The text advocates for a balanced framework: while the state centrally establishes the broad parameters of pricing policies to align corporate and national interests, production units must retain autonomous responsibility over pricing execution. This synthesis promotes cooperative commercial relations and adapts production to actual market demand.